1999
DOI: 10.1046/j.1463-5224.1999.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

The geographic form of retinal dysplasia in dogs is not always a congenital abnormality

Abstract: To examine the congenital nature of the geographic form of focal/multifocal retinal dysplasia, we carried out a retrospective analysis of the medical records of dogs produced in a closed colony of service dogs who receive very thorough ophthalmologic examinations early in their life, and later, when they return for training. Medical records were reviewed from all dogs produced by The Seeing Eye, Inc. between October 1991 and September 1998, and which had a diagnosis of geographic retinal dysplasia coded. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…The resulting lesions range in severity from multifocal RD, where histologically there is folding of retinal layers or duplication of one or more retinal neuronal layers, to more severe lesions including larger geographic regions of retinal malformation or even retinal detachment or nonattachment . RD has been reported as an inherited trait in several breeds of dog but may also result from environmental insults during retinal development including infection (e.g., canine herpesvirus), toxicity (e.g., vitamin A deficiency), and intra‐uterine irradiation . In most instances, lesions are present and detectable on examination of puppies at a few weeks of age, although one survey of dogs bred as leader dogs reported that lesions could develop or become apparent after the age at which the retina is mature …”
Section: Introductionmentioning
confidence: 99%
“…The resulting lesions range in severity from multifocal RD, where histologically there is folding of retinal layers or duplication of one or more retinal neuronal layers, to more severe lesions including larger geographic regions of retinal malformation or even retinal detachment or nonattachment . RD has been reported as an inherited trait in several breeds of dog but may also result from environmental insults during retinal development including infection (e.g., canine herpesvirus), toxicity (e.g., vitamin A deficiency), and intra‐uterine irradiation . In most instances, lesions are present and detectable on examination of puppies at a few weeks of age, although one survey of dogs bred as leader dogs reported that lesions could develop or become apparent after the age at which the retina is mature …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lesions typical of rd may become visible at different life stages. In a study by O'Toole et al (1983), dysplastic lesions in English Springer Spaniels were detected in an ophthalmoscopic examination straight after birth, whereas Holle et al (1999) found that in the case of geographic retinal dysplasia, the lesions were rarely noticeable earlier than week 10 of life, which may be associated with tapetal development which can last for up to the first 6 months of life (Cook 2013). It has been noted that single or multiple retinal folds may become less visible with age (Grahn et al 2004) or may disappear completely, after which the fundus returns to normal (ACVO Genetics Committee 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that single or multiple retinal folds may become less visible with age (Grahn et al 2004) or may disappear completely, after which the fundus returns to normal (ACVO Genetics Committee 2014). This is most probably associated with a redevelopment of the retina (O'Toole et al 1983;Cispin et al 1999;Holle et al 1999;Grahn et al 2004). Furthermore, because an ophthalmoscopic examination is subjective in nature, it gives rise to differences in how the fundus is evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations